Challenges in dual exceptionality’s diagnosis: a case study - Vilarinho-Rezende, Daniela (2016)
There is an increase in the number of children who are identified as gifted, and exhibit a learning disorder as well. This condition is known as dual exceptionality. However, there are few empirical studies about this topic. Therefore, the purpose of this article is to pres- ent a case study of a gifted child who was in the process of being diagnosed with Asperger Syndrome. Interviews were conducted with the child, the mother and professionals that served him. Psychological, neurological and phonological evaluations carried out with the boy were analyzed. The mother and professionals raised further explanations for the child’s behavior. The difficulties in the diagnostic process and the need for a multidisciplinary approach are explored.